Complex Science for a Complex World : Exploring Human Ecosystems with Agents - Perez, Pascal; Batten, David (Canberra ANU Press, 2006)
Human ecology; Australia
English
Keywords: Ecological science, the Biosphere; australia; human ecology; Agent-based model; Sustainability